Swedish housing - Hald, Arthur; Holm, Per; Johansson, Gotthard (Stockholm : Swedish Society of Arts and Crafts, 1949)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: huisvestingsbeleid; Zweden